Standardized health education program on breast self-examination : competence, confidence and compliance of female adolescents - Tamagos, Larry Joy C. (2001)
This study sought to determine the effectiveness of a standardized health education program in promoting breast self-examination (BSE) among female high school students of St. Michael's Institute, Bacoor, Cavite specifically on the adolescents' level of competence, level of confidence and level of compliance.Thirty two (32) female junior students of St. Michael's Institute of Bacoor, Cavite who met the inclusion criteria were the subjects for the study. The health education program consisted of (1) lecture-discussion about BSE and demonstration on breast self-examination conducted inside the classroom, plus an illustrated pamphlet to reinforce the classroom instructions. Data collections for hypothesis testing consisted of: (1) a 30-item multiple choice type questionnaire; (b) BSE skills checklist; and (c) two-month BSE compliance diary.Descriptive (measures of central tendency and dispersion) as well as inferential statistics (paired t-test) were utilized in the analysis of data. The study yielded the following results:a. On the total sampleThere was an increase in the level of competence, confidence and compliance on breast self-examination after the standardized health education program. Significant differences were found n the subjects' mean post-test scores over their pretest scores for level of competence. A significant difference was seen in the level of confidence two months after the program was instituted.b. On subjects categorized according to prior exposure to breast self-examinationThere were significant differences on the level of competence, confidence and compliance for both categories. However, subjects without prior exposure to BSE had higher mean scores for confidence than subjects who had prior exposure to BSE.The finding of the study show that the standardized health education program as that of Breast Self Examination for adolescents can be a valuable tool in health promotion and education, and eventually early detection of disease, in this case, breast cancer.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Health education -- Cavite